2021
DOI: 10.1186/s10020-021-00386-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of long non-coding RNA H19 in the development of osteoporosis

Abstract: Background Osteoporosis is a widespread and serious metabolic bone disease. At present, revealing the molecular mechanisms of osteoporosis and developing effective prevention and treatment methods are of great significance to health worldwide. LncRNA is a non-coding RNA peptide chain with more than 200 nucleotides. Researchers have identified many lncRNAs implicated in the development of diseases and lncRNA H19 is an example. Results A large amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 90 publications
(94 reference statements)
2
7
0
Order By: Relevance
“…The incidence of osteoporosis is 70% in people aged over 80 years and 15% in people over 50 years [ 3 ]. At present, there are more than 200 million patients suffering from osteoporosis worldwide; as life expectancy increases globally, osteoporosis will lead to increased financial and medical burdens in most countries, and it is expected that the global cost of osteoporosis may increase to $131.5 billion by 2050 [ 4 ]. Fragility fractures caused by low-energy trauma, particularly hip fracture, are common complications of osteoporosis that result in poor health-related quality of life and a high risk of disability and mortality [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of osteoporosis is 70% in people aged over 80 years and 15% in people over 50 years [ 3 ]. At present, there are more than 200 million patients suffering from osteoporosis worldwide; as life expectancy increases globally, osteoporosis will lead to increased financial and medical burdens in most countries, and it is expected that the global cost of osteoporosis may increase to $131.5 billion by 2050 [ 4 ]. Fragility fractures caused by low-energy trauma, particularly hip fracture, are common complications of osteoporosis that result in poor health-related quality of life and a high risk of disability and mortality [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…lnRNAs, due to their size (>200 kb), fold into secondary or tertiary structures to make them more flexible to target proteins. It has been discovered that lncRNA H19 plays a part in the control of various cell types in the body, including the osteoblasts, osteocytes, and osteoclasts found in bones (Chen et al, 2021). Therefore, it is conceivable that lncRNA H19 influences the occurrence and progression of osteoporosis.…”
Section: Regulation Of Osteoclastogenesismentioning
confidence: 99%
“…For instance, lncRNAs MALAT1, TUG1, and HOTAIR were reported to promote osteogenesis and bone formation [ 17 19 ]. As one of the earliest discovered lncRNAs, H19 plays crucial roles in various physiological and pathological activities [ 20 22 ]. Our previous study found that H19 promoted osteoblast differentiation through activating Wnt/ β -catenin signaling [ 23 ].…”
Section: Introductionmentioning
confidence: 99%